PENYULUHAN RUMAH PANGAN MANDIRI DI NAGARI SILANTAI, KECAMATAN SUMPUR KUDUS, KABUPATEN SIJUNJUNG, SUMATERA BARAT - Efrizal Efrizal; Nurmiati Nurmiati; Periadnadi Periadnadi; Ando Fernando (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
The purpose of this extension activity was to share experiences, the application of science, self-potential extraction and problem solving that occurs in the community, especially in agriculture. The method used is survey and observation, counseling, demonstration plot and direct training in field. Based on the survey and primary data from Nagari Silantai, it can be seen that the Nagari located in Sumpur Kudus District is geographically in the position of 0o26'49